1998
DOI: 10.1002/(sici)1097-0274(199804)33:4<327::aid-ajim3>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Proportionate mortality among union members employed at three Texas refineries

Abstract: The cause‐specific mortality (1940–1993) of 2,985 male workers employed in three oil refineries was examined using a proportionate mortality study design. Separate analyses were undertaken by race, refinery, employment status (active and retired), and time since entry into the Oil, Chemical, and Atomic Workers (OCAW) union. Proportionate cancer mortality ratio (PCMR) analyses also were conducted. Proportionate mortality ratios (PMR) were significantly increased (P < 0.05) for cancers of the lip (PMR = 384), st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Relative risks have been near unity in petroleum worker cohort studies in California, 177,178 Texas, [179][180][181] Louisiana, 182,183 US, [184][185][186] Canada 187,188 and Australia. 189 Inconsistent nonsignificant associations were found in an updated (1970-1997) mortality cohort study of 2 refinery/petrochemical plants (SMR for Baton Rouge facility 5 1.47, 95% CI: 0.98-2.11; SMR for Baytown facility 5 0.84, 95% CI: 0.47-1.39).…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%
“…Relative risks have been near unity in petroleum worker cohort studies in California, 177,178 Texas, [179][180][181] Louisiana, 182,183 US, [184][185][186] Canada 187,188 and Australia. 189 Inconsistent nonsignificant associations were found in an updated (1970-1997) mortality cohort study of 2 refinery/petrochemical plants (SMR for Baton Rouge facility 5 1.47, 95% CI: 0.98-2.11; SMR for Baytown facility 5 0.84, 95% CI: 0.47-1.39).…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%
“…English-language articles published in peer-reviewed journals up to October 2009 were included if relative risks of NHL associated with gasoline-exposed occupations/industries were reported with corresponding confidence intervals; or sufficient data were available to estimate these statistics. Reasons for exclusion were non-English articles [3] and studies which estimated proportional risks [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…In an analysis of construction injuries reported as workers' compensation cases, Dement et al, 18 Lipscomb and Li, 19 and Lombardi et al 20 compared the observed causes of injury among teen construction workers with those expected from a referent population of adult construction workers.…”
Section: Relationship To the Proportional Mortality Ratiomentioning
confidence: 99%